Still no bodies: Five years of "no body, no parole" in Queensland, Australia - Moffa, Monique (Journal of criminology, 2022)
?No body, no parole? laws have been introduced in and expanded across Australia since 2015. These reforms were politically premised on the notion of providing closure to victims? families by compelling prisoners convicted of homicide offences to disclose the location of their victims? remains in order to be considered eligible to apply for parole. These laws are in operation in most states and territories across Australia despite low national numbers of reported no body homicides. Most Australian jurisdictions do not publish parole decisions, and Queensland is one of only two jurisdictions that require no body, no parole decisions to be made public. This article reviews the roll-out of the ?no body? laws in Queensland and considers the potential to misuse the victims? movement for political gain. We examine the ten published decisions made by the Parole Board Queensland under s193A of the Corrective Services Act 2006 (Qld) to date and discuss the extent to which the legislative aims of the reforms have been met. We argue that there is little evidence these reforms have achieved their aims, and there is a risk that the politicization of parole regimes exploits the victims? rights movement by offering victims? families false hope.